Study of Local Business Development Model Based on Tempe Innovation Towards Food Security of Coastal Family Areas During the Covid-19 Pandemic - Yarmaliza Yarmaliza; Teungku Nih Farisni; Fitriani Fitriani; Fitrah Reynaldi; Zakiyuddin Zakiyuddin; Veni Nella Syahputri (LAFADZ JAYA Publisher, 2022)
The rapid spread of the COVID-19 pandemic has an impact on the world economy, including in the food and agricultural sectors. A 1% decline in China's economic growth in 2020 could have an impact of around 0.3% on the economy in Indonesia, and Aceh is no exception. Therefore, the creative economy stimulus is one of the most appropriate alternatives in overcoming the community's economic problems, by utilizing local commodities through innovation of tempeh powder broth as family food security in Purwodadi Village, Nagan Raya Regency. The purpose of this activity is to provide the importance of creative economic education for coastal communities, especially for poor families towards family food security during the COVID 19 pandemic. The method in this activity uses the FGD (Focus Group Discussion) approach and the PALS (Participatory Action Learning System) method. FGD is a process involving participants (local government, MSME actors and the community) where they exchange messages in a dialogical manner within the framework of a common understanding of the social situation. The results obtained in this activity are the existence of a local business development model based on tempeh innovation that can foster a spirit of independence to form Micro, Small and Medium Enterprises in coastal communities towards family food security during the COVID-19 pandemic.